Exercise Capacity and Balance in Patients with Anemic and Non-Anemic Chronic Obstructive Pulmonary Disease (COPD) - Mongkol, Sarayoot; Sookkua, Tichaporn; Kreeinthong, Sukanya (Journal of health and health management, 2026)
Chronic obstructive pulmonary disease (COPD) is a major public health problem associated with functional decline and reduced quality of life. Anemia is a common comorbidity in COPD and may further worsen physical performance, potentially increasing healthcare utilization and fall risk. The aim was to compare exercise capacity and balance performance among healthy individuals, non-anemic COPD patients, and anemic COPD patients. A cross-sectional study was conducted in 120 participants allocated into three groups: healthy controls (n = 40), non-anemic COPD patients (n = 40), and anemic COPD patients (n = 40). Exercise capacity was evaluated using the six-minute walk test (6MWT), and balance performance was assessed using the Timed Up and Go (TUG) test. Pulmonary function was measured by spirometry. Data were analyzed using one-way ANOVA with Bonferroni post hoc comparisons. The anemic COPD group demonstrated significantly shorter six-minute walk distance and longer TUG completion time compared with both non-anemic COPD patients and healthy controls (p < .05). Pulmonary function parameters were significantly lower in both COPD groups compared with controls, but did not differ between anemic and non-anemic COPD patients. Anemia is associated with additional functional limitations in COPD patients independent of airflow obstruction. Routine screening and integrated management of anemia may improve functional outcomes and support more effective rehabilitation planning in COPD care.